A preparative method of synthesis of pyrazolylphenyl(phenoxy)acetic acids - Moskvina, V.S.; Shilin, S.V.; Khilya, V.P. (Reports of the National Academy of Sciences of Ukraine, 2016)
A new convenient and accessible method of synthesis of 2-(1H-pyrazol-3-yl)phenols through the heterocyclization of enaminoketone acetophenones with hydrazine hydrate and N-methylhydrazine is developed. The reactivity of obtained compounds is studied. It is demonstrated that the alkylation reactions followed by the hydrolysis result in high yields and are a convenient approach to the synthesis of pyrazolylphenylacetic and (N-methylpyrazolyl-3(or 5)-yl)phenoxyacetic acids.